ANALISIS KELANGKAAN BBM PREMIUM DI PADANGSIDIMPUAN PERSPEKTIF HUKUM POSITIF DAN HUKUM EKONOMI SYARIAH - Nasruddin Khalil Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
Fuel (BBM) is a product or element that is vital in supporting the activities of community life. The scarcity of premium fuel (gasoline) is an obstacle in these activities. The majority of petrol stations in Padangsidimpuan have switched premium / gasoline to pertalite so that it has resulted in more expensive costs. This is very burdensome and detrimental to society. The approach method is juridical normative and nonprobability sampling design in the form of incidental sampling. The result of the research obtained is that it is necessary to form a regional regulation that regulates the rights and obligations of the parties, then if there is an act that violates the law by the SPBU (as a producer) that harms the public (consumers), administrative sanctions can be given in the form of temporary business license revocation and sanctions civil  form of compensation.